2019
DOI: 10.1590/0103-11042019s306
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of animal healthcare services waste in southern Brazil: One Health at risk

Abstract: Brazilian animal livestock is in full expansion but linked to the use of veterinary drugs which may be considered as emerging contaminants. The study aimed to characterize the disposal of Animal Healthcare Service Waste (AHSW), especially of veterinary drugs, besides identifying the most used drugs in the city of São Joaquim municipality, southern Brazil. Eighty-four cattle ranchers were interviewed through a structured questionnaire with closed questions about drugs use and disposal of the AHSW. The active in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Informações sobre o descarte dos resíduos de medicamentos na área rural ainda são escassas no Brasil, assim como o acesso da população rural as políticas de saneamento básico. Um estudo desenvolvido em um município serrano de Santa Catarina mostrou que resíduos de medicamentos de uso veterinário em propriedades rurais têm sido descartados de forma inadequada, como depositar no resíduo doméstico, enterrar, doar a outras pessoas, queimar ou colocar na pia/vaso (OLIVEIRA et al, 2019).…”
Section: Resultsunclassified
“…Informações sobre o descarte dos resíduos de medicamentos na área rural ainda são escassas no Brasil, assim como o acesso da população rural as políticas de saneamento básico. Um estudo desenvolvido em um município serrano de Santa Catarina mostrou que resíduos de medicamentos de uso veterinário em propriedades rurais têm sido descartados de forma inadequada, como depositar no resíduo doméstico, enterrar, doar a outras pessoas, queimar ou colocar na pia/vaso (OLIVEIRA et al, 2019).…”
Section: Resultsunclassified
“…Information about medicine waste disposal in rural area are yet scarce in Brazil, as politics to provide the rural population's access to sanitation. Research developed in a plateau municipality in Santa Catarina reported that veterinary medicine waste has been discarded inadequately in rural lands, as example discarding at home trash, burying, donating to other people or throw away into the sink/toilet (OLIVEIRA et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Mato Grosso, Goiás and Mato Grosso do Sul there is extensive production of soy, which is currently the crop that most consumes pesticides in Brazil 7 . In Santa Catarina, there is also intense use of pesticides, but the use is directed to apple cultivation mainly, in which an average of 35 applications per crop can occur 8 .…”
Section: Introductionmentioning
confidence: 99%